Detoxification of nitric oxide by the flavorubredoxin of Salmonella enterica serovar Typhimurium. (1st February 2005) - Mills, P.C.; Richardson, D.J.; Hinton, J.C.D.; Spiro, S.
Abstract : Salmonella possesses multiple enzymes that utilize NO as a substrate, and could therefore contribute to the organism's ability to resist nitrosative killing by macrophages. Flavorubredoxin is an oxygen-sensitive enzyme that reduces NO to nitrous oxide. The Salmonella enterica serovar Typhimurium norV gene encoding flavorubredoxin was disrupted and the NO sensitivity of the mutant was determined. The norV mutant showed a greater sensitivity to NO than wild-type S . Typhimurium, but did recover growth after a transient inhibition. The mutant phenotype suggests that multiple enzymes are employed by S . Typhimurium to detoxify NO under anaerobic conditions, one of which is flavorubredoxin.